Media Puzzle Sebagai Strategi Kreatif untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik pada Materi Penjumlahan - Putri, Prihastini Oktasari; Khoeriah, Siti Sifa (Indo-MathEdu Intellectuals Journal, 2025)
Mathematics learning at the elementary school level plays a crucial role in building a foundation for students logical thinking abilities. However, addition of numbers greater than 10 remains a challenge due to the cognitive limitations of students who are at the concrete operational stage. The aim of this study is to enhance students cognitive understanding through a creative strategy using puzzle media. This research was conducted using a Classroom Action Research (CAR) approach. The subjects of the study were 37 first-grade students at SDN Cintaasih. Data were collected through written test instruments. The results showed that students mastery increased from 40.5% in the pre-cycle, to 67.5% in the first cycle, and reached 86.4% in the second cycle. It can be concluded that first grade students at SDN Cintaasih experienced an improvement in cognitive learning outcomes in addition material after using puzzle media.